Targeted Delivery and Sustained Antitumor Activity of Triptolide through Glucose Conjugation. (30th August 2016) - He, Qing‐Li; Minn, Il; Wang, Qiaoling; Xu, Peng; Head, Sarah A.; Datan, Emmanuel; Yu, Biao; Pomper, Martin G.; Liu, Jun O.
Abstract: Triptolide, a key ingredient from the traditional Chinese medicinal plant thunder god vine, which has been used to treat inflammation and autoimmune diseases for centuries, has been shown to be an irreversible inhibitor of the XPB subunit of the transcription factor TFIIH and initiation of RNA polymerase II mediated transcription. The clinical development of triptolide over the past two decades has been limited by its toxicity and low water solubility. Herein, we report the development of a glucose conjugate of triptolide, named glutriptolide, which was intended to target tumor cells overexpressing glucose transporters selectively. Glutriptolide did not inhibit XPB activity in vitro but demonstrated significantly higher cytotoxicity against tumor cells over normal cells with greater water solubility than triptolide. Furthermore, it exhibited remarkable tumor control in vivo, which is likely due to sustained stepwise release of active triptolide within cancer cells. These findings indicate that glutriptolide may serve as a promising lead for developing a new mechanistic class of anticancer drugs.